Effect of zinc application on yield, dry matter production, nutrient uptake and soil available nutrients in bhendi (Abelmoschus esculentus (L.) Moench) - Jebisha, R; Coumaravel, K; Bagavathi, AU; Kanthaswamy, V (Plant Science Today, 2026)
The field experiment was carried out at Pandit Jawaharlal Nehru College of Agriculture and Research Institute, Karaikal, during the Rabi season of 2025 to investigate the influence of different zinc sources, application rates and methods on the growth, yield and quality of bhendi. Among the treatments, the integrated application of Zinc-Ethylenediaminetetraacetic Acid (Zn-EDTA) at 1.0 kg ha-1 as basal soil application combined with a 0.1 % foliar spray at 30 days after sowing (DAS) , along with recommended dose of fertilizer (RDF) and farmyard manure (FYM), produced the highest fresh fruit yield (19.33 t ha-1), representing a more than three-fold increase compared to the control (5.43 t ha-1).This treatment also enhanced nutrient uptake (N, P, K, Zn, Fe, Mn and Cu), indicating improved assimilation and nutrient-use efficiency. Post-harvest soil analysis revealed a balanced nutrient status, with higher Diethylene Triamine Penta acetic Acid (DTPA)-extractable micronutrient content at increased Zn-EDTA soil application levels, ensuring soil fertility sustainability. The findings highlight that integrated zinc management, particularly the use of chelated zinc, not only improves bhendi yield and quality but also enhances nutrient uptake and maintains soil nutrient balance, thereby serving as a viable strategy for boosting productivity and profitability of bhendi under intensive cultivation systems as demonstrated in the present study conducted under a randomized block design (RBD).